Febrile neutropenia after kidney transplantation. Issue 10 (10th July 2021) - Dube, Geoffrey K.; Morris, Heather K.; Crew, Russell J.; Pereira, Marcus R.; Cohen, David J.; Mohan, Sumit; Husain, Syed A.
Abstract : Neutropenia is common after kidney transplant. There are few data on febrile neutropenia episodes (FNE) after kidney transplant. We studied FNE in a single‐center retrospective cohort of 1682 kidney transplant recipients. Neutropenia (absolute neutrophil count [ANC] <1000) occurred in 32% and FNE in 3%. There were 56 FNE. Median time to FNE was 143 days, and median time from onset of neutropenia to onset of FNE was 5.5 days. The most common sources of infection were urine, blood, and lungs, and in 20% of FNE no source was identified. No infectious organism was identified in 46% of FNE, and opportunistic infections were uncommon. Patient survival was similar among those with and without FNE, but FNE was associated with increased death‐censored graft failure (DCGF). Following FNE, acute rejection occurred in 31% and DCGF in 15%, often in the setting of persistent reduced immunosuppression. In conclusion, FNE are common after kidney transplant and are associated with inferior long‐term outcomes. Abstract : Febrile neutropenia episodes in kidney transplant recipients frequently occur in the absence of an identifiable infectious organism or source of infection and are associated with an increased rate of subsequent acute rejection and death‐censored allograft failure.